A case of Osler-Weber-Rendu syndrome associated with portal hypertension - Surya, G. S. Sanjay; Venugopalan, Priya; Hanumanram, Gowtham; Mithra, Deepthi; Rajendran, Kannan; A., Gowrishankar (International Journal of Advances in Medicine, 2022)
Osler-Weber- Rendu syndrome is a rare autosomal dominant vascular disorder, characterised by multiple telangiectases of the skin and mucous membranes with recurrent nasal and gastrointestinal bleedings and arteriovenous malformations of various organ systems. It is also called as hereditary hemorrhagic telangiectasia (HHT). The occurrence of telangiectases in the stomach and small bowel can result in chronic bleeding and anaemia. We report a rare case of 39 year old female with Osler Weber Rendu syndrome associated with portal hypertension. She had recurrent nasal and gastrointestinal bleeding, and presented with complaints of progressive dyspnea NYHA class III. On further evaluation she was found to have portal hypertension, which is a rare association.